Development of multi-functional streetscape green infrastructure using a performance index approach - Tiwary, A; Williams, I D; Heidrich, O; Namdeo, A; Bandaru, V; Calfapietra, C (Environmental pollution (Barking, Essex, 2016)
This paper presents a performance evaluation framework for streetscape vegetation. A performance index (PI) is conceived using the following seven traits, specific to the street environments - Pollution Flux Potential (PFP), Carbon Sequestration Potential (CSP), Thermal Comfort Potential (TCP), Noise Attenuation Potential (NAP), Biomass Energy Potential (BEP), Environmental Stress Tolerance (EST) and Crown Projection Factor (CPF). Its application is demonstrated through a case study using fifteen street vegetation species from the UK, utilising a combination of direct field measurements and inventoried literature data. Our results indicate greater preference to small-to-medium size trees and evergreen shrubs over larger trees for streetscaping. The proposed PI approach can be potentially applied two-fold: one, for evaluation of the performance of the existing street vegetation, facilitating the prospects for further improving them through management strategies and better species selection; two, for planning new streetscapes and multi-functional biomass as part of extending the green urban infrastructure.
Keywords: Performance index; United Kingdom; Biomass; Decision Making; hluk; znečištění ovzduší; Air Pollution; Carbon Sequestration; Spojené království; City Planning; stromy; Multi-functional; rozhodování; sekvestrace uhlíku; ekosystém; Ecosystem; Pollution; Streetscape; Trees; biomasa; plánování měst; Noise; Green infrastructure